Decreased levels of spexin are associated with hormonal and metabolic disturbance in subjects with polycystic ovary syndrome. (3rd April 2021) - Guler, Aslı; Demir, İsmail
Abstract: Spexin, a newly identified peptide hormone, is involved in energy metabolism and the hypothalamic gonadal axis. We aimed to compare the altered levels of spexin in women with and without polycystic ovary syndrome (PCOS) and to find out if there was any association between spexin levels and hormonal-metabolic parameters in women with PCOS. Eighty subjects with PCOS and 80 age- and body mass index (BMI)-matched subjects with a normal menstrual cycle were enrolled into the current case control study. Spexin levels were measured by ELISA. Spexin levels were significantly lower in PCOS subjects. Spexin showed a negative correlation with insulin resistance, BMI and androgens in PCOS women. Binary logistic regression analysis showed that the risk of having PCOS was associated with low levels of spexin. Decreased spexin levels were inversely associated with androgens and unfavourable metabolic profiles in PCOS subjects, suggesting that the inter-related roles of spexin are in the different metabolic and hormonal pathways of PCOS. IMPACT STATEMENT: What is already known on this subjects? Spexin is a newly identified peptide hormone which plays various roles in regulating energy metabolism and the hypothalamic gonadal axis. PCOS is a reproductive and metabolic disorder associated with insulin resistance and hypothalamic-pituitary-gonadal axis disruptions. What do the results of this study add? Decreased levels of spexin were inversely association with androgens and unfavourable metabolic profiles in PCOS women. The risk of having PCOS was increased in parallel with decreased spexin levels. What are the implications of these findings for clinical practice and/or further research? Spexin may play numerous roles in the pathophysiological processes of PCOS. To find the exact role of spexin over PCOS development, detailed investigations are required.